CELEBRATING FLORES DE MAYO: AN IN-DEPTH LOOK AT THE CULTURE AND TRADITION IN BRGY. DANCALAN, DONSOL, SORSOGON. - Gilbert E. Lopez (Program Studi Tadris Bahasa Inggri Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
In the Philippines, Flores de Mayo is a well-known religious and cultural celebration that typically takes place in the month of May. The culmination of the month-long celebration is the Santacruzan procession, also referred to as the